PENGGUNAAN TEKNOLOGI IOT GPS TRACKING DALAM BISNIS DAN INDUSTRI LOGISTIK - Ari Pratama Putra; Jhon Veri (Journal of Innovation Research and Knowledge, 2025)
Technopreneur is the term for someone who runs a business by utilizing the latest technology and one of the impacts of this development is that it is implemented in the logistics industry which is also experiencing a significant transformation thanks to the development of Internet of Things (IoT) technology.. One of the prominent applications of IoT in logistics is GPS Tracking, which enables real-time monitoring of the location and condition of assets. This research examines the application of IoT GPS Tracking technology in the logistics sector, its impact on operational efficiency, cost reduction and increased customer satisfaction. This study also encourages the application of technology in Indonesia, including infrastructure and implementation costs. With a literature study approach, this article aims to provide insight into the strategic role of IoT GPS Tracking in supporting modern logistics.